COMPUTER SELF-EFFICACY AS A DETERMINANT OF SUCCESS OF MSME BUSINESS IN BANTUL REGENCY - Nicolas Rangga Pramudya; Muchran, Murniady; Hazmin, Gulam; Prasetyo, Adi; Haqi, Iqbal Aditya; Pronosokodewo, Baniady Gennody (Count : Journal of Accounting, Business and Management, 2024)
Finding out how computer anxiety, attitude, and self-efficacy affect the success of micro, small, and medium-sized enterprises (MSME) in Bantul Regency is the main goal of this study. Primary data is used in this quantitative study. The population for this analysis is all MSME actors in the Bantul Regency area, totaling 55 respondents. A purposive sample strategy was used in this research's sampling procedure. A criterion-based sample selection method is the purposeful sampling methodology. The data collection method in this research uses a questionnaire. The data analysis methods in the research are Validity Test, Reliability Test, Multiple Linear Regression, F Test, t Test, and Coefficient of Determination Test (R2). The research results show that computer anxiety has no effect on business success with a significance value of 0.940 > 0.05. Computer attitude has no effect on business success with a significance value of 0.865 > 0.05. Computer self-efficacy influences business success with a significance value of 0.002 <0.05. The results of this study indicate that computer anxiety and computer attitude are not significantly related to company performance. When it comes to the success of a company, one factor stands out: computer self-efficacy.